Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.1002/adom.202102057
|View full text |Cite
|
Sign up to set email alerts
|

Tunable Hyperbolic Phonon Polaritons in a Suspended van der Waals α‐MoO3 with Gradient Gaps

Abstract: Highly confined and low‐loss hyperbolic phonon polaritons (HPhPs) sustained in van der Waals crystals exhibit outstanding potential to concentrate the long‐wave electromagnetic fields deep into the subwavelength region. However, precise tuning on the HPhP propagation characteristics is a critical challenge to facilitate its practical applications in nanophotonic devices and circuits. This study, by taking advantage of the varying air gaps in a suspended van der Waals α‐MoO3 crystal, shows the feasibility to tu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 49 publications
0
16
0
1
Order By: Relevance
“…One of the practical means of controlling the dielectric environment is to transfer α-MoO 3 onto a prepatterned substrate consisting of areas of different dielectric constants. In this regard, by using the photothermal-induced resonance technique, Schwartz et al investigated the effective tuning of substrate-mediated PhP propagation characteristics in RB2 by placing α-MoO 3 on a SiO 2 substrate with periodic trenches, where it experiences two dielectric environments underneath, air and SiO 2 . Zheng et al reported the opposite dependence of the PhP wavelength (λ PhP ) on the air gap distance for gradiently suspended α-MoO 3 in RB2 and RB3. However, a systematic investigation of the impact of dielectric environment on the PhP propagation in both RB2 and RB3 of α-MoO 3 is still lacking, and the underlying mechanism remains elusive.…”
mentioning
confidence: 99%
“…One of the practical means of controlling the dielectric environment is to transfer α-MoO 3 onto a prepatterned substrate consisting of areas of different dielectric constants. In this regard, by using the photothermal-induced resonance technique, Schwartz et al investigated the effective tuning of substrate-mediated PhP propagation characteristics in RB2 by placing α-MoO 3 on a SiO 2 substrate with periodic trenches, where it experiences two dielectric environments underneath, air and SiO 2 . Zheng et al reported the opposite dependence of the PhP wavelength (λ PhP ) on the air gap distance for gradiently suspended α-MoO 3 in RB2 and RB3. However, a systematic investigation of the impact of dielectric environment on the PhP propagation in both RB2 and RB3 of α-MoO 3 is still lacking, and the underlying mechanism remains elusive.…”
mentioning
confidence: 99%
“…[33] Besides, the ambient dielectricity, such as the air gap (suspended) beneath the sample can also be detected through this polaritonic mode. [15,18,19,40] An inimitably latent functional application in α-MoO 3 falls in the energy range of 830-920 cm −1 , the lower band of RB2 and the upper band of RB1, where HPhPs launch in the form of an elliptic resonance-cone surface, and the "splitting mode" offers an operation to divide the HPhPs into a specific direction in real space. This property is promising for applications in light information transmission on the subwavelength scale.…”
Section: Resultsmentioning
confidence: 99%
“…(1) Among the four polaritons, experimental research on hyperbolic phonon polaritons (especially those appearing in hBN and α-MoO 3 ) 36,67,70,74,75,[77][78][79][140][141][142][143][144][145][146][147][148][149] is much more than on the other three polaritons. This could be due to the fact that hyperbolic phonon polaritons are the earliest discovered, and hBN and α-MoO 3 are relatively easier to achieve than the other 2D natural HMs.…”
Section: Discussionmentioning
confidence: 99%
“…The opposite alteration of polariton wavelengths in the lower and upper RBs has also been reported in gradually suspended α-MoO 3 . 79 As shown in Fig. 7(c), a nanoscale gradient air gap is formed between the SiO 2 substrate and the top α-MoO 3 flake.…”
Section: Hyperbolic Polaritons In 2d Natural Hmsmentioning
confidence: 91%